2016
DOI: 10.1007/s00221-016-4857-4
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and visual divergent thinking in aging

Abstract: According to the peak and decline model divergent thinking declines at a specific age (in or after middle age). However, if divergent thinking declines steadily in aging still has to be clarified. In order to explore the age-related changes in verbal and visual divergent thinking, in the present study a sample of 159 participants was divided in five age groups: young adults (18-35 years), middle-aged adults (36-55), young old (56-74), old (75-85) and the oldest-old (86-98). Two divergent thinking tasks were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 53 publications
4
43
0
2
Order By: Relevance
“…Previous research has shown that older adults have decreased cognitive creativity (Palmiero, Nori, & Piccardi, 2017) as well as other decreased cognitive abilities, like working memory, processing speed, reasoning and higher-level executive functions (Salthouse et al, 2003;Salthouse, 2010). The present study contributes to this field and shows that age was negatively associated with the ECI total score and two components of the ECI, emotional novelty and emotional preparedness.…”
Section: Resultssupporting
confidence: 62%
“…Previous research has shown that older adults have decreased cognitive creativity (Palmiero, Nori, & Piccardi, 2017) as well as other decreased cognitive abilities, like working memory, processing speed, reasoning and higher-level executive functions (Salthouse et al, 2003;Salthouse, 2010). The present study contributes to this field and shows that age was negatively associated with the ECI total score and two components of the ECI, emotional novelty and emotional preparedness.…”
Section: Resultssupporting
confidence: 62%
“…In sum, the current findings suggest that short-term and cost effective interventions, such as CT, may be beneficial in enhancing cognitive capacities and supporting neural mechanisms in healthy older adults. The new finding related to improved innovative cognition in healthy older adults is heartening; given innovative thinking is one of the most valued assets and fruitful outputs of the human mind across the lifespan (Kaufman and Sternberg, 2006 ; Palmiero et al, 2016 ). The potential to strengthen innovative cognition may tap into a positive and valuable resource of the aging mind that could support an individual’s ability to reinforce and retain an active mental lifestyle, engage in complex decision-making, intellect and psychological well-being with advancing age (Baltes et al, 1999 ; Kaufman and Sternberg, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Innovative cognition is widely recognized as a vital capacity, undergirding adaptive and flexible thinking. This cognitive domain is of interest in older adults due to its centrality to human cognition, intellect, decision-making, life achievement, resilience and psychological well-being (McFadden and Basting, 2010 ; Li et al, 2015 ; Beaty et al, 2016 ; Heilman, 2016 ; Palmiero et al, 2016 ; Saggar et al, 2016 ). Innovative thinking may be a pivotal cognitive capacity and brain function allowing one to respond effectively to challenging and constantly changing life demands (Saggar et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The age of the participants is categorized into three age groups—young adults (1 = aged 20–35 years), middle-aged adults (2 = aged 36–55 years), and older adults (3 = aged 56 years and older). This categorization of age groups was adopted from the previous studies which investigated various relevant topics including health behavior change and aging aspects ( Petry, 2002 ; Palmiero et al, 2017 ; Wang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Age groups should be analyzed in regard to whether young adults (i.e., 20–35 years) differ from middle-aged adults (i.e., 36–55 years) and the aging older adults that included both young-old- and oldest-old adults (i.e., older than 56 years). This grouping approach was chosen by previous study related to health behavior change ( Petry, 2002 ; Ziegelmann et al, 2006 ), and some studies which are related to the aspects of aging ( Palmiero et al, 2017 ; Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%